Foreign language acquisition focused on kindergarten pupils - Pipicz Anett (2003)
This thesis examines language acqusition focused on kindergarten pupils between the ages of four and six. I am going to make paralelles with the characterictics of this age group and language acquisition. I am also going to talk about the special care and education they need. The caracteristics of young children allow us to use a great variety of exercises, they are so accomodating, that a language teacher can take a good advantage of this- theoretically. These ideas are going to be included in the first part. In the second part I am going to demonstrate how second language acquisition in the kindergarten ideally works, however the third part will include some bad examples of teaching English to very young learners. Concerning the very poor situation I have met, it can be stated that the kindergarten teaching phenomenon is still in its infancy. Using my own experiences, and the research I have made in different kindergartens I am going to support how effective second language learning can be.